‘Feminization’ of physician workforce in Bangladesh, underlying factors and implications for health system: Insights from a mixed-methods study. - Hossain, Puspita; Gupta, Rajat Das; YarZar, Phyoe; Jalloh, Mohamed Salieu; Tasnim, Nishat; Afrin, Ayesha; Naher, Nahitun; Hossain, Md. Tarek; Joarder, Taufique; Ahmed, Syed Masud (PLOS ONE, 2022)
This article was published in the PLOS ONE [© 2019 Hossain et al. This is an open access article distributed under the terms of the Creative Commons Attribution License ] and the definite version is available at: https://doi.org/10.1371/journal.pone.0210820 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0210820